Transdermal patch for boil treatment using a combination of ethanol extracts from Hibiscus sabdariffa and Aloe barbadensis - Indi Agus Riani; Mirna Artin Setya Rahayu; Laelita Chaya Valentine; Septiani Sherly Angely; Reza Nurjanah; Dina Febrina (Universitas Ahmad Dahlan, 2026)
Boils (furuncles) are skin infections brought on by Staphylococcus aureus, characterized by inflamed, pus-filled lumps. Plants like roselle (Hibiscus sabdariffa) and aloe vera (Aloe barbadensis) that have antibacterial and anti-inflammatory properties may be used in treatment. When combined, they could have a more potent synergistic impact than when used separately in order to assess their antibacterial and anti-inflammatory activities. Three formulations were prepared: F1 (EER 0.5 g, EEAV 0.5 g), F2 (EER 1 g, EEAV 0.5 g), and F3 (EER 1.5 g, EEAV 0.5 g). The antibacterial activity was tested using the well-diffusion method, and the anti-inflammatory effects were evaluated in a rabbit cutaneous infection model induced by S. aureus. The patches exhibited characteristic aromas, smooth textures, and darker hues as the EER concentration increased. All formulas complied to the physical quality standards, with an average weight of 159.11 ± 16.56 mg and a thickness of 0.39 ± 0.08 mm. The F3 patch exhibited the most potent antibacterial activity (16.00 mm inhibition zone) and the most significant reduction in inflammation. One-way ANOVA results revealed a p-value of 0.000 (p < 0.05), indicating statistically significant differences in antibacterial and anti-inflammatory effects among the formulas.